Comparing the Language Style Used by Native and Non-native English Speakers in The Ellen Show - Cahyanti, Ade Dwi; Hartono, Rudi; Linggar Bharati, Dwi Anggani (Universitas Negeri Semarang, 2021)
As the user of communication especially in English, the speaker has to consider the interlocutor’s position in order to achieve good communication. Here, the speakers which include native and non-native English speakers must choose an appropriate language style for the different interlocutors to avoid social consequences. The purposes of this research were to analyze the use of language style of those speakers in The Ellen Show. Also, it focused on the differences and the similarities between those speakers. Last, it focused on the factors influencing the use of language style. The research used the qualitative method which focuses on content analysis. Here, it focused on three native speakers and three non-native speakers of English as the guests in The Ellen Show. The Ellen Show is a talk show program with a casual discussion that talks about a particular topic or issue which consists of a host, the guest(s) being interviewed, the home audience, and the studio audience from which the host might get some responses from.The findings revealed that the native English speakers used all types of language styles. Meanwhile, the non-native speakers used three types of language styles. Then, the similarities were that both speakers applied formal style, consultative style, and casual style in their utterances. However, the difference was the non-native English speakers did not apply frozen style and intimate style. Furthermore, those speakers used language style because it influenced the participant, the setting, the topic, and the function. Therefore, it is concluded that language styles were useful in English utterances either by native speakers or non-native English speakers. The speaker has to consider the interlocutor’s position in order to achieve good communication. Here, the speakers which include native and non-native English speakers must choose an appropriate language style for the different interlocutors to avoid social consequences. The purposes of this research were to analyze the use of language style of those speakers in The Ellen Show. Also, it focused on the differences and the similarities between those speakers. Last, it focused on the factors influencing the use of language style. The research used the qualitative method which focuses on content analysis. Here, it focused on three native speakers and three non-native speakers of English as the guests in The Ellen Show. The findings revealed that the native English speakers used all types of language styles. Meanwhile, the non-native speakers used three types of language styles. Then, the similarities were that both speakers applied formal style, consultative style, and casual style in their utterances. However, the difference was the non-native English speakers did not apply frozen style and intimate style. Furthermore, those speakers used language style because it influenced the participant, the setting, the topic, and the function. Therefore, it is concluded that language styles were useful in English utterances either by native speakers or non-native English speakers.